Validation of a short‐form of the Freiburg Life Quality Assessment for lymphoedema (FLQA‐LS) instrument3. (5th October 2018) - Augustin, M.; Conde Montero, E.; Hagenström, K.; Herberger, K.; Blome, C.
Summary: Background: Chronic lymphoedema (CLE) is a burdensome disease of multiple causes leading to significant reductions in health‐related quality of life (HRQoL). A specific method to assess HRQoL is the Freiburg Life Quality Assessment for lymphoedema (FLQA‐L), which consists of 92 items. Objectives: To develop and validate a short form of the FLQA‐L with improved psychometric properties and feasibility. Methods: The FLQA‐L validation data were reanalysed by patients and experts. The application of factor analysis enabled the exclusion of lower‐load items. An optimized short version of the questionnaire (FLQA‐LS) with 33 items was generated and tested in a validation study on patients with different forms of CLE. Results: In total, 348 patients with CLE of the upper or lower extremities were included (mean age 57.3 years, range 24–89; 90.8% female), and data from 301 patients could be analysed. Overall, 42.8% of the patients had secondary lymphoedema, 23.6% had primary lymphoedema, 9.5% had lipoedema and 24.1% had lipolymphoedema. The lower extremities were mostly affected (64.4% of the patients presented with leg involvement and 17.5% with both arm and leg impairment). The FLQA‐LS showed good internal consistency, with high Cronbach's alpha in the subscales and in the global scale ranging between 0.79 and 0.94. Regarding convergent validity, a good correlation was found with the general HRQoL questionnaire EQ‐5D ( r = 0.72, P < 0.001). Conclusions: FLQA‐LS is an improved version of the FLQA‐L questionnaire for chronic lymphoedema. It demonstrated validity and feasibility and can be easily used in clinical practice and research studies. Abstract : What's already known about this topic? Lymphoedema is a chronic, burdensome condition that markedly impairs health‐related quality of life. What does this study add? A short form of the Freiburg Life Quality Assessment for lymphoedema (FLQA‐LS) is a valid and feasible instrument to measure health‐related quality of life in patients with lymphoedema.What are the clinical implications of this work? Linked Comment: Chalmers. Br J Dermatol 2018;179 :1244–1245 . Plain language summary available online Respond to this article